2021
DOI: 10.3389/fpsyg.2021.729835
|View full text |Cite
|
Sign up to set email alerts
|

Victims of Bullying: Emotion Recognition and Understanding

Abstract: Introduction: Victims of bullying often show interpersonal problems, such as having less high-quality interpersonal relationships compared to non-involved individuals. Research suggests that interpersonal struggles are associated with diminished emotional intelligence and competence and can lead to mental health problems such as depression. Therefore, we examined emotion recognition abilities, empathic accuracy, and behavioral responses to emotions in bullying victims and non-involved individuals. Based on pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Some studies investigating PE, such as pride and hope, obtain results that confirm the increased perception of academic success [ 49 , 50 ]. According to Fredrickson [ 51 ], EPs enhance the acquisition of more personal resources for complex tasks that are present in teaching–learning processes [ 50 ]. The activation of these emotions allows students to perceive successful task performance, as opposed to negative emotions that are related to perceptions of failure [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies investigating PE, such as pride and hope, obtain results that confirm the increased perception of academic success [ 49 , 50 ]. According to Fredrickson [ 51 ], EPs enhance the acquisition of more personal resources for complex tasks that are present in teaching–learning processes [ 50 ]. The activation of these emotions allows students to perceive successful task performance, as opposed to negative emotions that are related to perceptions of failure [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The highest scores in PE were observed in the non-victim aggression category, while the victim with aggression category showed the lowest scores in PE. Other studies have more generally observed that experiences related to bullying in some way are associated with difficulties in regulating emotions, suggesting alterations in students’ emotional intelligence, which may persist into adulthood [ 50 , 51 ]. However, it should be noted that those who fell under the victim with aggression category, in addition to showing the lowest scores in PE, were those who showed the lowest AP according to a previous article with the same sample of students, where statistically significant differences were also observed with respect to the categories of bullying and AP [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, bullies will be less likely to bully others, thus reducing the occurrence of school bullying. At the same time, some scholars believe that ( Canas et al, 2020a , b ; Leon-del-Barco et al, 2020 ; Franzen et al, 2021 ) emotional intelligence is a protective factor of school bullying, and has a key role to play in promoting students’ emotional adjustment and understanding ability.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies that found that negative childhood experiences that were associated with abuse situations influence the development of specific biases in emotional processing 38 , 39 , we hypothesized that there would be greater emotional reactivity over time, reflected by EPN and LPP components, in victims of bullying compared with bullies and observers.…”
Section: Introductionmentioning
confidence: 99%